Gender and age differences in expression peer violence - Blagojević, Gordana D.; Marjanovic, Bogdan S. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2023)
The complex problem of peer violence has been the subject of many research studies so far. The prevalence, forms, and manifestation forms of peer violence, causes, and consequences have been intensively studied. This paper describes and examines the occurrence of violence, considering both gender and age differences. The research has been carried out on a representative sample of 204 pupils of both sexes, in the fifth and eighth grades, who attend two primary schools. The results of the research show that a greater tendency, towards violent behaviour between boys and girls, has been confirmed (t=5.83, p<0.01). Statistically significant difference, in the tendency to violent behaviour between the pupils of different ages, that is, fifth and eighth graders, has been identified It shows us that eighth graders have a significantly greater tendency to violent behaviour than fifth graders This research is important because its results can be used, to improve our knowledge about the violent behaviour of pupils, in the school environment, as well as to encourage us to take the best course of practical action and to adopt prevention models in this area.